2012
DOI: 10.1165/rcmb.2010-0500oc
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylarginine Deiminases Present in the Airways during Tobacco Smoking and Inflammation Can Citrullinate the Host Defense Peptide LL-37, Resulting in Altered Activities

Abstract: Bacterial colonization of the lower respiratory tract is frequently seen in chronic obstructive pulmonary disease (COPD), and may cause exacerbations leading to disease progression. Antimicrobial peptides comprise an important part of innate lung immunity, and not least the cathelicidin human cationic antimicrobial protein-18/LL-37. Peptidylarginine deiminases (PADIs) post-translationally modify proteins by converting cationic peptidylarginine residues to neutral peptidylcitrulline. An increased presence of PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 49 publications
8
97
1
Order By: Relevance
“…It has been estimated that one hundred thousand activated neutrophils secrete around 10 ng ml À1 of cathelicidin in 15 min culture (Jann et al, 2009), whereas we observed in the present study that similar number of islet cells secrete around 80 pg ml À1 of cathelicidin in overnight culture. Second, we suggest that, as many proteins of the NETs (Wang et al, 2009), cathelicidins produced by activated neutrophils might be citrullinated, while cathelicidins expressed by endocrine cells were not and it has been shown that this post-translation modification suppresses the immunoregulatory properties of cathelicidins (Kilsgå rd et al, 2012;Koziel et al, 2014). Collectively, these data support that the diverse cellular source and associated post-translational modifications of cathelicidins might explain their opposite roles in inflammation.…”
Section: Discussionmentioning
confidence: 58%
“…It has been estimated that one hundred thousand activated neutrophils secrete around 10 ng ml À1 of cathelicidin in 15 min culture (Jann et al, 2009), whereas we observed in the present study that similar number of islet cells secrete around 80 pg ml À1 of cathelicidin in overnight culture. Second, we suggest that, as many proteins of the NETs (Wang et al, 2009), cathelicidins produced by activated neutrophils might be citrullinated, while cathelicidins expressed by endocrine cells were not and it has been shown that this post-translation modification suppresses the immunoregulatory properties of cathelicidins (Kilsgå rd et al, 2012;Koziel et al, 2014). Collectively, these data support that the diverse cellular source and associated post-translational modifications of cathelicidins might explain their opposite roles in inflammation.…”
Section: Discussionmentioning
confidence: 58%
“…phosphatidylcholine derivatives, taurine and peptidyl arginine deiminase (PAD)). PAD deiminates cathelicidin and impairs the antimicrobial activity against NTHI (130). We observed increases in both the chinchilla ortholog of human antimicrobial peptide-cathelicidin (15 kDa protein A-like) and PAD during AOM (Table I).…”
Section: Discussionmentioning
confidence: 79%
“…In this context smoking, and possibly other inhaled pro-inflammatory agents, have been reported to promote protein citrullination in the lungs, a process mediated by peptidylarginine deiminase (PAD) enzymes [27][28][29][30]. PADs convert positively charged protein arginine residues to neutral, potentially immunogenic citrulline.…”
Section: Smoking and Ramentioning
confidence: 99%